Prokaryotic 5'-3' exonucleases share a common core structure with gamma-delta resolvase. - Artymiuk, P J (1997)
The three dimensional crystal structure of T5 5'-3' exonuclease was compared with that of two other members of the 5'-3' exonuclease family: T4 ribonuclease H and the N-terminal domain of Thermus aquaticus DNA polymerase I. Though these structures were largely similar, some regions of these enzymes show evidence of significant molecular flexibility. Previous sequence analysis had suggested the existence of a helix-hairpin-helix motif in T5 exonuclease, but a distinct, though related structure is actually found to occur. The entire T5 exonuclease structure was then compared with all the structures in the complete Protein Data Bank and an unexpected similarity with gamma-delta (gamma delta) resolvase was observed. 5'-3' exonucleases and gamma delta resolvase are enzymes involved in carrying out quite different manipulations on nucleic acids. They appear to be unrelated at the primary sequence level, yet the fold of the entire catalytic domain of gamma delta resolvase is contained within that of the 5'-3'exonuclease. Different large-scale helical structures are used by both families to form DNA binding sites.